OPTIMASI PENGENDALIAN BANJIR DI KOTA TANGERANG DENGAN METODE GOAL PROGRAMMING DAN AHP (ANALYTICAL HIERARCHY PROCESS) - Shiddiq Waluyo; Saiful Haq (Universitas Muhammadiyah Tangerang, 2016)
Floodingproblems tend toincrease from yearto yearprimarily due tochangesin landuse andthe rapiddevelopmentofhumanactivitiesinthe floodplain.Floodsthat occurred wouldhave anegative effectandisbadforanareawhere peoplesuffered greatlossesinthematerial.This studyaimstodeterminetheweightofeachpriority risk factorsinaneffort tominimize therisk offloodinginthecity ofTangerangusing GoalProgrammingandAHP(AnalyticalHierarchy Process).Thisresearchwas conducted in the city of Tangerang, Banten Province and type of research is descriptive exploratoryresearch,usingqualitative dataanalysismethod.Results showedthattherisk factorscontrollingriverhasthegreatestweightie44%,arisk factorforboththeneedstakenseriouslyisarunoffwithaweightof19%,arisk factor forallthreethatneedsattentionisthemanagementofwatershedswithaweightof17%,which isasimportantasrisk factorscatchments10%,the fourthrisk factoris habits ofpeople with aweightof 4%,and thefifth riskfactor that is siltingup the river with a weightof 4.Keywords:floods,thepriorityweight,thenegativeimpact,riskfactors,methodsofGoal Programming and AHP